2022
DOI: 10.21511/imfi.19(1).2022.21
|View full text |Cite
|
Sign up to set email alerts
|

Financial constraints and corporate governance as moderating variables for the determinants of tax avoidance

Abstract: The purpose of this study is to empirically investigate the effect of financial constraints and corporate governance as moderating variables on the determinants of tax avoidance, which includes foreign activity, corporate social responsibility, and political connections. All companies listed on the Indonesia Stock Exchange from 2017 to 2019 are the objects of this study. The panel data regression was used to address the research question. The findings show that foreign activity, corporate social responsibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Similarly, Farooq (2020) also found that board gender diversity improves access to finance, reduces liquidity risk problem and improves financial performance of firms. In another research, audit committee effectiveness and board independence reduces financial and liquidty problems (Silvera et al, 2022;Tessema, 2019). Also, Lee and Byun (2017) study revealed that board characteristics and audit features have positive relationship with financial constraints and liquidity of firms.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, Farooq (2020) also found that board gender diversity improves access to finance, reduces liquidity risk problem and improves financial performance of firms. In another research, audit committee effectiveness and board independence reduces financial and liquidty problems (Silvera et al, 2022;Tessema, 2019). Also, Lee and Byun (2017) study revealed that board characteristics and audit features have positive relationship with financial constraints and liquidity of firms.…”
Section: Introductionmentioning
confidence: 92%
“…It suggests that their existence in family businesses limits investment prospects for those businesses through internal cash flow or external loan funding, which over time lowers the long-term worth of the business. The impact of financial constraints and corporate governance as moderator on the causes of tax avoidance, which include international trade, corporate social responsibility, and political ties in Indonesia, was also experimentally examined by (Silvera et al, 2022). The research revealed that political ties, social responsibility, and overseas operations all had a big impact on tax avoidance.…”
Section: Review Of Empirical Studies and Hypotheses Developmentmentioning
confidence: 99%
“…Tax avoidance is considered an unethical act because it interferes with the government's ability to provide public facilities and infrastructure which are financed through tax revenues [16]. Tax avoidance is carried out by exploiting gaps in existing tax regulations [17].…”
Section: The Effect Of Political Connection On Tax Avoidancementioning
confidence: 99%
“…Businesses facing financial constraints will usually pursue an optimal cash strategy to balance the returns on current investments with the returns on future investments. They expect future financing constraints by reinvesting cash from current profits, so companies facing financial constraints will grow their cash holdings to ensure future sustainability, which can be achieved in part by reducing tax payments [16]. By taking advantage of the advantages that come with being politically connected, the zombie corporation can stay afloat.…”
Section: Political Connections Zombie Firm and Tax Avoidancementioning
confidence: 99%
“…; Hermawan (e.g., Richardson et al, 2015;Abdillah et al, 2019;Wang et al, 2020;Salehi et al, 2020;Riguen et al, 2021;Jin et al, 2022;Silvera et (Donohoe and Robert, 2014;Martinez and Lessa, 2014;Tehupuring, 2016;Bae, 2017;Hu, 2018;Wang et al, 2020;Gontara and Khlif, 2021;Clara, 2022…”
mentioning
confidence: 99%